Provenancing of pottery from Kamuiyaki Site in East Asia by neutron activation analysis - Sterba, Johannes H.; Shinoto, Maria; Shinzato, A.; Enomoto, M.; Yomine, Y. (Archaeometry, 2021)
A set of 20 vessels was selected from the Japanese National Historical Site ‘Kamuiyaki Kiln Site Cluster’. Selection was performed with explicit archaeological problems and the potential of instrumental neutron activation analysis (INAA) in mind. The set was analysed by INAA and subsequent statistical data analysis adapted to the specific problems of ceramics and applied for the first time in Kamuiyaki. Chemical fingerprinting allowed the a priori separation of the set of samples into two chemically distinct groups that had a clear correlation with the archaeological and chronological data. This indicates that at least two different recipes or sediments were used in the cluster, which can now be identified among the several hundred external sites where sherds are recorded as supposedly produced at Kamuiyaki.